Mycorrhization of vitroplants raised from somatic embryos of cork oak (Quercus suber L.) - Dı́ez, Jesús; Manjón, José Luis; Kovács, Gabor M.; Celestino, Cristina; Toribio, Mariano (Applied Soil Ecology, 2000)
The technique described herein allows in vitro ectomycorrhizal synthesis in Quercus suber vitroplants raised from somatic embryos with Pisolithus tinctorius and Scleroderma polyrhizum strains. Only strains of this species coming from fruit bodies collected in Quercus suber stands (strain QS241 and strain QS247) formed ectomycorrhizas, and hence these species seem to exhibit host adaptation. The in vitro mycorrhization facilitated the development of secondary roots and the ex vitro weaning of cork oak vitroplants.
Keywords: Cork oak; ectomycorrhizas; Mycorrhization; Somatic embryogenesis